Physico-Chemical Aspects of the Processes During the Combustion and Heating of Tobacco under Different Conditions (A Review) - Idrizi, M.; Achevski, B.; Godzo, H.; Mitic, K.; Pejov, Lj.; Tonic Ribarska, J. (Asian Journal of Chemistry, 2023)
Smoking cigarettes causes lung cancer, heart disease, chronic obstructive pulmonary disease (COPD) and other serious diseases. The damage caused by cigarette smoking is multifaceted and complex. Exposure to harmful and potentially harmful constituents (HPHCs), created during the process of burning tobacco, is the main reason for the development of smoking-related diseases. An alternative way to reduce the generation of toxicants from tobacco product is to heat rather than burn tobacco. Modified risk tobacco product (MRTP) are designed to significantly reduce or eliminate the release of harmful and potentially harmful chemicals while preserving, as much as possible, taste, sensory experience, nicotine delivery profile, and the ritual component of smoking cigarettes. In this review, the chemical composition of the smoke generated by conventional cigarettes to the composition of the aerosol generated by devices for controlled tobacco heating is compared. Also, critically assess the current knowledge in the field, aiming towards an objective assessment of the alternative tobacco products.
Keywords: Tobacco smoke, Modified risk tobacco products, Combustion, Heated tobacco products.